Formation and Development of a Foreign Primary School in Yakutsk Region in Second Half of the XIX - Early XX Centuries - Agrafena I. Makarova (Научный диалог)
The formation of state policy in the field of foreign primary education in the second half of the XIX - early XX centuries on the example of the Yakutsk region is considered in the article. It is noted that until the middle of the 19th century the state took its time to develop the education system on foreign outskirts, then during the liberal reforms of the 1860-1870s the government paid special attention to foreign education. It is reported that in total for the period under review four legislative documents were adopted on the education of non-Russian peoples with the aim of unifying the multinational school system and their integration into the common imperial social space. Based on archival documents, the formation and development of primary schools in the region is shown. Information on the number of schools and the number of students, the characteristics of the types of educational institutions, the conditions of their maintenance and activities are given. It was determined that the variety of types of schools, the inconsistency of provisions and charters made it difficult to guide them. Particular attention is paid to the territorial, climatic factors, lack of teaching staff, which had a great influence on the formation and development of the educational system in the region. It is concluded that, despite a number of specific problems, primary public education in the Yakutsk region developed as an integral part of the all-Russian educational process.